Current Status of Magnetoelectric Composite Thin/Thick Films - Rahul C. Kambale; Dae-Yong Jeong; Jungho Ryu (Advances in Condensed Matter Physics)
Here we review the current status of magnetoelectric (ME) multiferroics and ME composite thin/thick films. The magnitude of ME coupling in the composite systems is dependent upon the elastic coupling occurring at the interface of piezoelectric and magnetostrictive phases. The multiferroic ME films in comparison with bulk ME composites have some unique advantages and show higher magnitude of ME response. In ME composite films, thickness of the films is one of the important factors to have enough signal. However, most of all reported ME nanocomposite structured films in literature are limited in overall thickness which might be related to interface strain resulting from difference in thermal expansion mismatch between individual phases and the substrate. We introduced noble ME composite film fabrication technique, aerosol deposition (AD) to overcome these problems. The success in AD fabrication and characterization of ME composite films with various microstructure such as 3-2, 2-2 connectivity are discussed.